Of Resurrection and Surveillance: Politics and Imaginaries of Literary Heritage in Early Pahlavi Iran - Ghajarjazi, Arash (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2026)
This article examines how modern ideas about and experiences with surveillance were formed in twentieth-century Iran by close reading and contextualizing the first modern science fiction in Persian literature, written by ‘Abd al-Ḥosayn San’atizāda in 1937 in Iran. This novella, Rostam in the Twenty-second Century, is a humorous commentary on the emerging modern surveillance in Pahlavi Iran. This article analyses the novella’s narrative strategies as a lens into the formation of Pahlavi surveillance. It begins by outlining the rudimental development of a surveillance regime as the state increasingly sought to monitor and control the public sphere, regulating not only people’s appearance and behavior but also their understanding of the past and their collective memory. Drawing from media theory, this state-based development is conceptualized as “surveillance dispositive,” which aims to detail how the Pahlavi state apparatus remediated and enforced a new national literary heritage as a strategy to observe and control the Iranian populations. The article then examines how this surveillance dispositif shaped emerging social experiences with state supervision and control. Drawing on surveillance studies and taking the novella as the primary object of analysis, it invokes the concept of the “surveillance imaginary” to elucidate how Iranian society grappled with a new condition of being watched under the Pahlavi surveillance regime. The novella is shown to diagram a narrative abstraction that reveals the relationship between the surveillance dispositif and its corresponding imaginary.